Efficacy of expressed breast milk, facilitated tucking, and their combination for pain management during heel stick in preterm neonates: a randomized controlled trial - Das, Rupam; Deshmukh, Vikrant; Sohane, Arpit; Suryawanshi, Pradeep; Deshmukh, Rupeshkumar; Malshe, Nandini (Frontiers in Pediatrics, 2025)
BackgroundHeel-stick procedures for glucose monitoring are common in neonatal intensive care units (NICUs) and can have adverse physiological and developmental effects on preterm neonates. The National Neonatology Forum of India and the American Academy of Pediatrics recommend the routine use of non-pharmacological measures during such procedures. Our study aimed to evaluate the efficacy of expressed breast milk (EBM), facilitated tucking (FT), and their combination in reducing heel stick pain in preterm neonates, as assessed using the Premature Infant Pain Profile (PIPP) score at 1 and 4 min post-procedure.MethodsIn this randomized controlled trial, preterm neonates born between 27 and 36+6 weeks of gestation, who met the eligibility criterion, were randomly allocated into three categories: EBM (n = 56), FT (n = 56), and EBM + FT (n = 56), following approval from the Institutional Ethics Committee and parenteral consent at a tertiary-level NICU in Pune. Neonates were videotaped by a senior resident/clinical fellow for 2 min before and up to 4 min after the heel-stick procedure. Infants’ pain was determined using the PIPP score at the time of heel-sticking and at 1 and 4 min post-procedure.ResultsRepeated-measures ANOVA revealed significant reductions in pain scores from baseline (EBM: 8.55 ± 3.19, FT: 8.63 ± 2.83, and EBM + FT: 9.46 ± 2.82; p < 0.001) to both 1 min (EBM: 5.68 ± 2.77, FT: 6.39 ± 3.17, and EBM + FT: 6.45 ± 2.87; p < 0.001) and 4 min (EBM: 4.05 ± 1.85, FT: 4.66 ± 2.59, and EBM + FT: 4.82 ± 2.39; p < 0.001) post-procedure. Bonferroni post-hoc analyses confirmed significant within-group reductions in pain across all time points.ConclusionsEBM and FT, whether alone or in combination, are effective in reducing pain in preterm neonates during heel-stick procedures.Clinical Trial Registrationhttps://ctri.nic.in/Clinicaltrials/login.php, identifier [CTRI/2023/09/057787 (Registered on: 18/09/2023)].